DEVELOPMENT OF AN INTEGRATED DIGITAL GUIDANCE AND COUNSELING MANAGEMENT APPLICATION FOR STRENGTHENING STUDENTS' MORAL DEVELOPMENT IN ISLAMIC SENIOR HIGH SCHOOLS - Kurniawan Kurniawan; Muhammad Khoiruddin; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The rapid advancement of digital technology has transformed educational management, including guidance and counseling (GC) services. However, many Islamic senior high schools still rely on fragmented and manual counseling administration, resulting in inefficient documentation, limited stakeholder collaboration, and inadequate monitoring of students' behavioral and moral development. This study aimed to develop an Integrated Digital Guidance and Counseling Management Application to improve counseling effectiveness while strengthening students' moral development. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observations, interviews, documentation, questionnaires, and expert validation involving counselors, teachers, school leaders, students, parents, and information technology experts. The developed web-based application integrates student profiles, counseling records, behavioral monitoring, disciplinary management, parent communication, reporting systems, and executive dashboards into a centralized information system. The implementation results indicate that the application improves administrative efficiency, facilitates collaboration among educational stakeholders, supports evidence-based decision-making, and enables continuous monitoring of students' behavioral and moral development. The novelty of this study lies in integrating digital counseling management with Islamic moral education within a comprehensive educational management system specifically designed for Islamic senior high schools. The application is expected to contribute to digital transformation in educational management and enhance the quality of guidance and counseling services.